PENGARUH PERBEDAAN PADAT TEBAR LARVA TERHADAP PERTUMBUHAN DAN SINTASAN PADA IKAN UCENG (NEMACHEILUS FASCIATUS) - Subagja, Jojo; Prakoso, Vitas Atmadi; Arifin, Otong Zenal; Kristanto, Anang Hari (Research Center for Biology-Indonesian Institute of Sciences, 2019)
Proper stocking density on larval rearing of barred loach (Nemacheilus fasciatus Valenciennes, 1846) is very important in terms of obtaining the best growth and survival rate. This study was aimed to observe the growth and survival rate of barred loach subjected to different larval stocking density. Fish larvae were obtained by artificial spawning from in aquarium. Larvae were stocked on aquariums (50 × 40 × 30 cm) with three stocking density treatments (5, 10, and 15 individuals/L) and three replications. The experimental fish larvae were fed by Artemia and commercial feed (crude protein content: 30%) and feeding frequency twice per day (ad libitum). The length and weight were reassured every 10 days during 70 days of rearing period. Temperature, pH, and dissolved oxygen were measured at each treatment. Data obtained from measurements were analysed to assess the length gain, weight gain, specific growth rate (SGR), biomass gain, and survival rate. The results showed length gain of 3.35 ± 0.01, 2.94 ± 0.10, and 2.82 ± 0.15 cm and weight gain of 0.573 ± 0.023, 0.436 ± 0.018, and 0.417 ± 0.043 g in larval stocking density of 5, 10 and 15 individuals/L, respectively. Specific growth rates and biomass growth were of 6.22 ± 0.41, 5.93 ± 0.21, and 5.68 ± 0.41 %/day and 94.04 ± 5.39, 146.80 ± 3.81, and 167.24 ± 17.48 g in larval stocking density of 5, 10 and 15 individuals/L, respectively. Meanwhile, the survival rates obtained in this study were 89.13 ± 7.25, 93.13 ± 5.13, and 76.50 ± 3.54 % in larval stocking density of 5, 10 and 15 individuals/L, respectively. Increased stocking density has a negative impact on the growth and survival rate of barred loach.